(untitled) (Global Journal of Science Frontier Research, 2014)
Beverage companies are used stainless steel in their manufacturing operations. Generally beverage companies make wine, beer and various types of soft drink. Their transportation and storage can be done in stainless steel containers. Beverage industries use different types of raw materials for the productions wine, beer and soft drink. They are acidic nature and their pH occur between5.5 to 6.5. Some preservatives are also added into these drinks for prevention of microorganism. These preservatives have acidic character. Wine, beer, soft drink and preservatives develop corrosion cell on the surface stainless steel thus corrosion reaction starts and harmful metal ions go into solution in this way these drinks contaminated. The contaminated drinks create several diseases. Corrosive effects are of remarkable consequence in beverage processing industry as wine, beer and soft drink contain corrosive substances, thereby causing significant impact on the degradation of constructional materials and the maintenance or replacement of products lost or contaminated as a result of corrosion reactions.